Functional characterization of various algal carotenoid ketolases reveals that ketolating zeaxanthin efficiently is essential for high production of astaxanthin in transgenic Arabidopsis - Zhong, Yu-Juan (Oxford University Press, 2011)
Extending the carotenoid pathway to astaxanthin in plants is of scientific and industrial interest. However, expression of a microbial β-carotene ketolase (BKT) that catalyses the formation of ketocarotenoids in transgenic plants typically results in low levels of astaxanthin. The low efficiency of BKTs in ketolating zeaxanthin to astaxanthin is proposed to be the major limitation for astaxanthin accumulation in engineered plants. To verify this hypothesis, several algal BKTs were functionally characterized using an Escherichia coli system and three BKTs were identified, with high (up to 85%), moderate (∼38%), and low (∼1%) conversion rate from zeaxanthin to astaxanthin from Chlamydomonas reinhardtii (CrBKT), Chlorella zofingiensis (CzBKT), and Haematococcus pluvialis (HpBKT3), respectively. Transgenic Arabidopsis thaliana expressing the CrBKT developed orange leaves which accumulated astaxanthin up to 2 mg g(−1) dry weight with a 1.8-fold increase in total carotenoids. In contrast, the expression of CzBKT resulted in much lower astaxanthin content (0.24 mg g(−1) dry weight), whereas HpBKT3 was unable to mediate synthesis of astaxanthin in A. thaliana. The none-native astaxanthin was found mostly in a free form integrated into the light-harvesting complexes of photosystem II in young leaves but in esterified forms in senescent leaves. The alteration of carotenoids did not affect chlorophyll content, plant growth, or development significantly. The astaxanthin-producing plants were more tolerant to high light as shown by reduced lipid peroxidation. This study advances a decisive step towards the utilization of plants for the production of high-value astaxanthin.